2014
DOI: 10.1097/brs.0000000000000433
|View full text |Cite
|
Sign up to set email alerts
|

C7–T1 Anterior Closing Wedge Bone-Disc-Bone Osteotomy for the Treatment of Cervical Hyperlordosis in Muscular Dystrophy

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…An anterior cervical spine locking plate was used for achieving stabilization. Kose et al [9] reported three cases of anterior closing wedge osteotomy for the treatment of cervical hyperlordosis. The anterior vertebral column was exposed firstly, and C7–T1 closing wedge osteotomy was performed using the disc as a hinge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An anterior cervical spine locking plate was used for achieving stabilization. Kose et al [9] reported three cases of anterior closing wedge osteotomy for the treatment of cervical hyperlordosis. The anterior vertebral column was exposed firstly, and C7–T1 closing wedge osteotomy was performed using the disc as a hinge.…”
Section: Discussionmentioning
confidence: 99%
“…Sengupta et al [1] reported a case of flexion osteotomy of the cervical spine for correction of iatrogenic extension deformity in ankylosis. Kose et al [9] reported three cases of anterior closing wedge osteotomy for the treatment of cervical hyperlordosis.…”
Section: Introductionmentioning
confidence: 99%
“…Diebo et al 5 observed that the restoration of global sagittal alignment after the correction of cervical deformity in EDMD during 8-year follow-up. Coincidentally, Kose et al 7 reported similar clinical outcomes in Becker muscular dystrophy (BMD), wherein sagittal alignment was restored after correction of cervical deformity. They all considered that the cervical hyperlordosis could be the driver of global sagittal malalignment, and suggested that cervical deformity should be dealt with first.…”
Section: Pathological and Genetic Diagnosismentioning
confidence: 94%
“…11,12 Contracture of the cervical extensors, especially combined with contracture of paraspinal ligaments, can lead to cervical hyperextension. 3,11 Additionally, Kose et al 7 reported difficulty moving into the osteotomy line when they attempted to raise patient's head for closing the osteotomy line after anterior cervical osteotomy, because of existence of rigid posterior cervical soft tissue. Therefore, performing posterior surgery first for sufficient release of soft tissue may be a better option.…”
Section: Pathological and Genetic Diagnosismentioning
confidence: 99%
“…Kose et al . [14] reported that BDBO was performed at the C7-T1 level to correct an extension deformity of the cervical spine in patients with muscular dystrophy who presented clinically with debilitating hyperlordosis; the procedure resulted in significant acute clinical and radiological improvement.…”
mentioning
confidence: 99%